2013
DOI: 10.12988/asb.2013.13004
|View full text |Cite
|
Sign up to set email alerts
|

Studies on bacillus subtilis, as potential probiotics, on the biochemical parameters of rainbow trout, oncorhynchus mykiss (walbaum) to challenge infections

Abstract: In this study Bacillus subtilis is used for control of streptococcosis with the agent of Streptococcus iniae in Rainbow trout. The experience was carried out in 2 groups (Control and Treatment) and 3 replicates. In Control group, probiotic was not applied in diet but in Treatment group, Bacillus subtilis was administered in feed at a concentration of 10 7 cells g-1. In the day of forty five, 0.1 ml intraperitoneally injection of S.iniae with 2×10 7 cells ml-1 dosage was done for both of groups and were checked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 35 publications
9
12
0
Order By: Relevance
“…In the present study, albumin concentration significantly improved at 2% and 4% ACV and 0.5% PA groups; meanwhile, it is slightly higher in shrimp fed 1% ACV diet compared with control diet. In confirmation described results, albumin and total protein concentrations were significantly increased in L. vannamei when fed with the diet containing Bacillus subtilis (Kamgar & Ghane, 2013). However, a raise of albumin concentration led to the hypothesis that dietary supplementation with ACV and PA improved nutritional value.…”
Section: Discussionsupporting
confidence: 74%
“…In the present study, albumin concentration significantly improved at 2% and 4% ACV and 0.5% PA groups; meanwhile, it is slightly higher in shrimp fed 1% ACV diet compared with control diet. In confirmation described results, albumin and total protein concentrations were significantly increased in L. vannamei when fed with the diet containing Bacillus subtilis (Kamgar & Ghane, 2013). However, a raise of albumin concentration led to the hypothesis that dietary supplementation with ACV and PA improved nutritional value.…”
Section: Discussionsupporting
confidence: 74%
“…The genus Bacillus has been identified in many studies to be a common part of the core microbial community of the fish gut (Austin and Al‐Zahrani ; Cahill, ; Ringø et al ; Kim et al ) and widely applied as a probiotic in aquaculture due to its ability to stimulate the host immune system, produce antimicrobial compounds, and other useful substances such as digestive enzymes, amino acids, etc. (Newaj‐Fyzul et al ; Wang et al ; Olmos and Paniagua‐Michel, ; Kamgar et al ).…”
Section: Discussionmentioning
confidence: 99%
“…A neighbor joining dendrogram generated using the sequence from the selected actinomycete (1400 bp) and representative sequences from the databases revealed that it belonged to Streptomyces spp. Pearl millet flour has been used for isolation of LAB (Badau, 2006;Kamgar et al, 2013;Okoronkwo, 2014). Microbes such as Lactobacillus, Bifidobacterium and Weissella spp.…”
Section: Discussionmentioning
confidence: 99%